RISKS IN THE MANAGEMENT OF INVESTMENT AND INNOVATIVE PROJECTS - E. Bogomolova (Publishing House of the State University of Management, 2019)
This article considers aspects of risk management in projects related to investment and innovative direction. These projects are associated with obtaining a high return on invested capital, but as you know, the higher the profit, the higher the level of risks affecting the results of the project during its implementation. Therefore, the considered theme is relevant, as in recent years, more projects are implemented with a high degree of innovativeness and the use of high technologies in their implementation.